Analisis Sistem Informasi Manajemen Pada Sistem Enterprise Terhadap Bisnis Pengembangan Era Modern - Arya Agiltriawan; Raihan Wakasara; Isa Faqihuddin Hanif (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
In the modern era marked by rapid technological developments, enterprise systems play a crucial role in improving business efficiency and competitiveness. This study analyzes the role of enterprise systems in supporting business strategies, increasing productivity, and optimizing the management of company resources. The research method used is a qualitative approach with literature studies and case study analysis from various companies that have implemented enterprise systems. The results of the study indicate that the implementation of enterprise systems, such as Enterprise Resource Planning (ERP) and Customer Relationship Management (CRM), can provide significant benefits in decision making, business process automation, and increased coordination between departments. However, challenges such as implementation costs, system complexity, and the need for employee training are also factors that must be considered in the adoption of this technology. Therefore, the right implementation strategy and adjustment to business needs are key factors in the success of enterprise systems in supporting business development in the modern era.